Singapore Management University Report to Stakeholders 2014 - 2015 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2015)
This has been a landmark year for both Singapore and Singapore Management University (SMU) with SG50 and SMU15 celebrations marking the nation's 50 years and University's 15 years of progress respectively. The University was honoured to host Singapore’s Prime Minister Mr Lee Hsien Loong who delivered the 7th Ho Rih Hwa Leadership in Asia Public Lecture. This was especially poignant as Singapore’s first Prime Minister Mr Lee Kuan Yew gave the series’ inaugural lecture in 2002. Mr Lee Hsien Loong discussed the significant challenges facing Singapore over the next 50 years. You can read about his thought-provoking lecture in one of three feature articles. Another feature article highlights SMU President Professor Arnoud De Meyer’s 2015 State of the University Address. Making “SMU Vision 2025 – Engage” his inspirational theme, Professor De Meyer outlined the University’s progress since he revealed SMU Vision 2025 a year ago. He was delighted that many students, faculty and staff had made significant contributions and encouraged everyone to be actively engaged to bring the University to its next level of development.